The characteristics of blood glucose and WBC counts in peripheral blood of cases of hand foot and mouth disease in China: a systematic review. - Yuyun Li (Public Library of Science (PLoS), 2012)
Background Outbreaks of Hand Foot and Mouth Disease (HFMD) have occurred in many parts of the world especially in China. We aimed to summarize the characteristics of the levels of blood glucose and white blood cell (WBC) counts in cases of HFMD in Mainland China and Taiwan, using meta-analysis based on systematic review of published articles. Methods We systematically reviewed published studies, from the MEDLINE and WANFANG Data, about the levels of blood glucose and WBC counts in cases of HFMD until 15(th) June 2011, and quantitatively summarized the characteristics of them using meta-analysis. Results In total, 37 studies were included in this review. In Mainland China and Taiwan, generally, the average level of blood glucose, the prevalence of hyperglycemia, WBC counts and the prevalence of leukocytosis increased with the severity of the illness. There was no significant difference in the prevalence of leukocytosis between ANS (autonomic nervous system dysregulation)/PE (pulmonary edema) group and CNS (central nervous system) group, and in the average level of blood glucose between healthy controls and mild cases of HFMD. WBC counts in cases infected by EV71 were less than those in cases infected by CA16. Conclusions our analyses indicated that blood glucose and WBC counts increased with the severity of HFMD disease, which would help doctors to manage patients efficiently.